2021
DOI: 10.1186/s12959-021-00297-4
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation abnormalities in childhood acute lymphoblastic leukemia: assessing the impact of L-asparaginase therapy in Ghana

Abstract: Background Although the rate of childhood acute lymphoblastic leukemia (ALL) is increasing in Africa, there is a dearth of information on the disease and the dynamics of hemostatic parameters with therapy. Methods In this case-control study, we evaluated variations in the level/activity of selected coagulation parameters among cALL in Ghana and healthy controls stratified by stage of therapeutic management. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This contrasts with a prior study that reported increased PT and APTT in ALL patients compared with a control group; such increase might be related to chemotherapy-associated decreases in coagulation factors. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with a prior study that reported increased PT and APTT in ALL patients compared with a control group; such increase might be related to chemotherapy-associated decreases in coagulation factors. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with a prior study that reported increased PT and APTT in ALL patients compared with a control group; such increase might be related to chemotherapy-associated decreases in coagulation factors. 31 Study limitations. This study investigated the prevalence and hematological characteristics of hematological malignancies in the southern region of Saudi Arabia.…”
mentioning
confidence: 99%